2016
DOI: 10.3892/ijo.2016.3759
|View full text |Cite
|
Sign up to set email alerts
|

Expression of metallothionein 3 in ductal breast cancer

Abstract: Metallothionein 3 (MT-3) has the ability to regulate the growth of nerve cells, but the significance of MT-3 expression outside the central nervous system and its participation in carcinogenesis have not yet been clarified. The aim of our study was to investigate the expression of MT-3 in ductal breast cancer and to determine its relationship with well-defined clinicopathological factors in this type of tumor. The study was conducted on 134 cases of invasive ductal breast carcinoma (IDC), 42 samples of non-mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 61 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…A decrease in MT3 expression was observed in pituitary adenocarcinoma with spinal cord metastasis [ 87 ]. Likewise, Gomulkiewicz et al showed that the MT3 expression was significantly lower in patients with ductal breast cancer with lymph node metastasis than in patients without metastasis [ 88 ]. Furthermore, Fu et al demonstrated a significant positive association of MT1G hypermethylation with lymph node metastasis in 178 papillary thyroid cancer patients [ 89 ].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in MT3 expression was observed in pituitary adenocarcinoma with spinal cord metastasis [ 87 ]. Likewise, Gomulkiewicz et al showed that the MT3 expression was significantly lower in patients with ductal breast cancer with lymph node metastasis than in patients without metastasis [ 88 ]. Furthermore, Fu et al demonstrated a significant positive association of MT1G hypermethylation with lymph node metastasis in 178 papillary thyroid cancer patients [ 89 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metallothionein (MT) is a protein that has been widely studiedas a prognostic marker for breast cancer, since it promotes apoptosis, proliferation and differentiation of malignant tumor cells, making them more resistant to treatment 810 . Studies suggest that overexpression of metallothionein is associated with more aggressive breast tumors and more advanced-stage disease 1114 .…”
Section: Introductionmentioning
confidence: 99%
“…Sens et al showed that MT-3 over-expression was detected in breast cancer samples, and it was found to be associated with high recurrence rate (Sens, et al, 2001). In another study, however, MT-3 expression has been found to be lower in IDBC specimens compared with non-malignant breast tissues or mastopathies, in addition, the level of MT-3 mRNA was demonstrated to be even lower in breast cancers with lymph node metastasis than in carcinomas without metastasis (Gomulkiewicz, et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…Noteworthy, they also revealed a negative correlation between invasiveness of ERα+ cells (MCF-7) and MT-1F and MT-1M expression, which thus may play an anti-oncogenic role. Distinct role was identified for MT-3, which is commonly silenced in normal breast tissue and breast-derived cell lines, but can be found in breast cancers tending to poor disease outcome (Gomulkiewicz, et al, 2016;Kmiecik, et al, 2015;Zeisig, Koklic, Wiesner, Fichtner, & Sentjurc, 2007). Interestingly, Somji et al revealed that treatment of non-tumorigenic MCF-10A cells with demethylation agent Decitabine or histone deacetylase inhibitor, Entinostat, restored the expression of MT-3 (Somji, et al, 2010), suggesting its epigenetic regulation.…”
Section: Epigenetic Alterations Due To Dna Methylation Processesmentioning
confidence: 99%